PERAWATAN KESEHATAN RONGGA MULUT IBU HAMIL DI PUSKESMAS TRENGGALEK JAWA TIMUR - Dian Rahmawati; Ovi Pifiana Mayong (Bahasa Indonesia, 2017)
Oral health care is a series of activities to maintain oral health which are performed correctly in accordance with the individual condition. Particularly, oral care becomes a crucial activity for pregnant women. This study aims to describe the pregnant women’s oral health in TheHealth Center of Trenggalek of Jawa Timur. This study used descriptive research design with cross sectional approach. The study was implemented on 1-27 of May, 2017 in The Health Center of Trenggalek of Jawa Timur. The population comprises all pregnant women which amounted to 40 respondents. The samples were taken by using total sampling technique. The variable was the pregnant women’s oral health in The Health Center of Trenggalek of Jawa Timur. Check list used of the instrument. The data processing consists of editing, coding, scoring, and tabulating. The data was analyzed by using percentage. The study finding showed that there were 6 respondents (15%) who had Gingivitis, 15 respondents (37.5%) who had Granuloma, and 19 respondents (47.5%) who experienced Caries. From the study concluded that most pregnant women had poor oral health condition. Consequently, the health workers should perform oral health care counselor particularly for pregnant women.